Exploring Dehumanization in Ted Hughes' Poem Hawk Roosting Through an Eco-Critical Lens - Perveen Sonia Mahid; Muhammad Daffa Farhan; Nuril Eka Yuanda; Purwarno Purwarno (ITScience (Information Technology and Science), 2024)
This study aims to investigate the theme of power dehumanization portrayed through the perspective of the Hawk in Ted Hughes' poem, Hawk Roosting. Hughes vividly depicts the Hawk's tyrannical nature and arrogance, positioning him as the ultimate authority, with the entirety of the universe subject to his dominance. The eco-critical approach within the poem is discernible through its intricate depiction of the Hawk's natural habitat, unveiling a lush and complex forest ecosystem. The research reveals that nature is not merely a passive backdrop in this poem; rather, it emerges as an active participant, mirroring the interconnectedness and vitality of the environment. Through the lens of the Hawk, the poem presents a unique outlook on the natural hierarchy, with the Hawk assuming the role of the uncontested ruler. It underscores humanity's inclination to exert absolute control over nature, mirroring the Hawk's behavior, often disregarding the long-term repercussions of such dominance. Moreover, the poem emphasizes the resilience and potency of nature, challenging human assertions of superiority. By adopting an eco-critical perspective, the poem prompts a reassessment of the Hawk's oppressive demeanor, while fostering an appreciation for the diversity and intricacy of the ecosystem that sustains human life.